2020
DOI: 10.3892/ol.2020.11805
|View full text |Cite
|
Sign up to set email alerts
|

A meta‑analysis of the added value of diffusion weighted imaging in combination with contrast‑enhanced magnetic resonance imaging for the diagnosis of small hepatocellular carcinoma lesser or equal to 2 cm

Abstract: Diffusion weighted imaging (DWI) has been found to increase the sensitivity in the diagnosis of small hepatocellular carcinoma (HCC), although additional studies are required to confirm its value. The aim of the present study was to explore the diagnostic performance of DWI combined with contrast-enhanced magnetic resonance imaging (MRI) for small HCC by performing a meta-analysis. Literature databases (PubMed, Embase, Web of Science and Cochrane Library databases) were searched to identify studies reporting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Studies with WB-DWI showed a significantly higher sensitivity for cancer treatment assessment than those without (0.94 vs. 0.55, p = 0.02 at univariate metaregression and p = 0.012 at multivariate meta-regression). This is not surprising since DWI is a multipotent imaging modality for cancer diagnosis (30), staging (31), and treatment response assessment (32). Previous studies showed that ADC value increased significantly in responders compared to nonresponders (5,33).…”
Section: Discussionmentioning
confidence: 99%
“…Studies with WB-DWI showed a significantly higher sensitivity for cancer treatment assessment than those without (0.94 vs. 0.55, p = 0.02 at univariate metaregression and p = 0.012 at multivariate meta-regression). This is not surprising since DWI is a multipotent imaging modality for cancer diagnosis (30), staging (31), and treatment response assessment (32). Previous studies showed that ADC value increased significantly in responders compared to nonresponders (5,33).…”
Section: Discussionmentioning
confidence: 99%
“…DWI offers functional quantitative data on the tissue's microstructure by means of the water proton mobility differences and cellular density evaluation. Water diffusion mobility is linked to cell density, vascularity and viscosity of the extracellular apparent diffusion coefficient (ADC), and it's possible to identify imaging biomarkers for fibrosis, tumor fluid and cell membrane integrity using a mono-exponential model or with diffusion and perfusion parameters in a bi-exponential model [104][105][106][107][108][109][110][111][112][113][114]. Using an Intravoxel Incoherent Motion method (IVIM) bi-exponential model to analyze DWI data, it is possible to obtain the pure tissue coefficient (Dt) linked only to diffusion water mobility, the pseudo-diffusion coefficient (Dp) linked to blood mobility, and the perfusion fraction (fp) [115][116][117][118][119][120][121][122].…”
Section: Diffusion Weighted Imaging-mrimentioning
confidence: 99%
“…DWI shows diffusion restriction in areas of high cellularity and cell membrane density (for example, malignancy) (27). DWI increases the sensitivity of conventional extracellular contrast-enhanced MRI, especially for small (<2 cm) HCCs (28). Sensitivity for HCC with gadoxetic acid contrastenhanced MRI is improved (95.2%) when including wash-out criteria for the hepatobiliary phase (29).…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%